2008
DOI: 10.1096/fj.07-105353
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia induced by methionine supplementation does not independently cause atherosclerosis in C57BL/6J mice

Abstract: A causal relationship between diet-induced hyperhomocysteinemia (HHcy) and accelerated atherosclerosis has been established in apolipoprotein E-deficient (apoE −/− ) mice. However, it is not known whether the proatherogenic effect of HHcy in apoE −/− mice is independent of hyperlipidemia and/or deficiency of apoE. In this study, a comprehensive dietary approach using C57BL/6J mice was used to investigate whether HHcy is an independent risk factor for accelerated atherosclerosis or dependent on additional dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
31
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 52 publications
7
31
0
3
Order By: Relevance
“…15 Plasma homocysteine levels of CSE-KO mice fed with the control or atherogenic diet were 18 times higher than those of age-matched WT mice, which is in line with our previous study. 20 Zhou et al 35 reported that dietinduced hyperhomocysteinemia does not independently cause atherosclerosis in C57BL/6J mice. In our study, no significant change was observed in plasma hyperhomocysteinemia levels after NaHS treatment of CSE-KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…15 Plasma homocysteine levels of CSE-KO mice fed with the control or atherogenic diet were 18 times higher than those of age-matched WT mice, which is in line with our previous study. 20 Zhou et al 35 reported that dietinduced hyperhomocysteinemia does not independently cause atherosclerosis in C57BL/6J mice. In our study, no significant change was observed in plasma hyperhomocysteinemia levels after NaHS treatment of CSE-KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that dietary effects on HDL levels are different in humans and mice. In humans, most cholesterol is carried in LDL, whereas mice carry most of their plasma cholesterol in HDL (37). Therefore, the relationship between tracer uptake and HDL levels and the species differences with regard to this point remain to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…However, hyperhomocysteinemia has been observed to potentiate the development of atherosclerosis in susceptible strains of mice, such as hyperlipidemic Apoe Ϫ/Ϫ mice 37 or C57BL/6 mice fed an atherogenic diet containing cholate. 84 Hofmann et al reported that Apoe Ϫ/Ϫ mice fed a hyperhomocysteinemic diet developed atherosclerotic lesions in the aortic sinus that were of greater size and complexity than those seen in Apoe Ϫ/Ϫ mice fed normal chow. 37 Several other investigators, using a variety of dietary and genetic approaches to induce hyperhomocysteinemia in Apoe Ϫ/Ϫ mice, have confirmed and extended the observations of Hofmann.…”
Section: Vascular Phenotypes Of Hyperhomocysteinemic Micementioning
confidence: 99%